Trypanotolerance in East African Orma Boran cattle - Njogu, A.R.; Dolan, R.B.; Wilson, A.J.; Sayer, P.D. (Wiley, 1985)
Comparative studies on two types of East African zebu (Bos indicus) Boran cattle, on a beef ranch in Kenya, have indicated that a Boran type bred by the Orma tribe has a superior response to tsetse fly challenge. The Orma Boran when compared with an improved Boran was found to have lower trypanosome infection rates and, when untreated, better control of anaemia and decreased mortality.